1983
DOI: 10.1042/bj2120093
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of non-esterified fatty acids in isolated hepatocytes from newborn and young pigs. Evidence for a limited capacity for oxidation and increased capacity for esterification

Abstract: In hepatocytes isolated from 48 h-old starved of suckling newborn pigs or from 15-day-old starved piglets, the rate of ketogenesis from oleate or from octanoate is very low. This is not due to an inappropriate fatty acid uptake by the isolated liver cells, but results from a limited capacity for fatty acid oxidation. Some 80-95% of oleate taken up is converted into esterified fats, whatever the age or the nutritional conditions. Three lines of indirect evidences suggest that fatty acid oxidation is not control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 35 publications
2
39
1
Order By: Relevance
“…BHB levels in the present study were in the lower range to previously reported values for hepatocytes isolated from 60 kg pigs (Fernández-Fígares et al, 2004). The low rate of β-oxidation capacity has been ascribed to a propensity for fatty acid esterification v. oxidation in piglets (Pégorier et al, 1983). As ketone bodies are the result of partial free fatty acid oxidation, no differences in fatty acid oxidation would be expected between pig breeds at the hepatic level.…”
Section: Bhb Synthesiscontrasting
confidence: 71%
“…BHB levels in the present study were in the lower range to previously reported values for hepatocytes isolated from 60 kg pigs (Fernández-Fígares et al, 2004). The low rate of β-oxidation capacity has been ascribed to a propensity for fatty acid esterification v. oxidation in piglets (Pégorier et al, 1983). As ketone bodies are the result of partial free fatty acid oxidation, no differences in fatty acid oxidation would be expected between pig breeds at the hepatic level.…”
Section: Bhb Synthesiscontrasting
confidence: 71%
“…In the hepatocyte model, it is clear that available carnitine markedly limits the rate of palmitate oxidation and this may indicate that at least following 4 days of culture, cellular levels of carnitine are attenuated. In other hepatocyte studies where fatty acid utilization has been investigated, carnitine has been routinely added to the extracellular environment presumably to ensure maximal rates of oxidation (Pegorier et al, 1983;Odle et al, 1991). When betaine was added to carnitine-free and carnitine amended cultures, no enhancement of oxidation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, such a study was partially performed in acute conditions from venous blood sampling (Ruiz, Ewan and Speer, 1971 ;Atinmo, Pond and Barnes, 1974 (Pégorier et al, 1983). Stable concentrations of blood metabolites are found after the first postoperative day but later concerning plasma insulin.…”
Section: Introductionmentioning
confidence: 99%